Management report: is it a component of financial, nonfinancial or integrated reporting? - I.V. Zhyhlei; D.M. Zakharov (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The new requirements of the Law «On Accounting and Financial Reporting» demand enterprises to publish the «Management Report» in order to supplement the annual financial statements with information that should help users obtain reliable data on the results of activities, development prospects, major risks, achievement of declared objectives and strategic plans.The combination of financial and non-financial information is typical for integrated reporting, which has recently emerged in world-wide reporting practice. The article analyzes how legislative changes can sort out the issues that exist in Ukrainian reporting practice, as well as identify problems that may arise at the enterprises in the process of publishing new reporting. It is determined that in order to improve the quality of the «Management Report», western practice should be taken into account. The conclusions were made based on the comparative analysis of non-financial reports of Ukrainian and world companies. When preparing a report for an enterprise it is important to determine its form, since the form itself influences the expansion of the user’s circle, increasing their loyalty and consolidating a positive reputation at the market. The global trends of development of reporting point to the fact that integrated reporting is becoming widespread, as it accurately disclose information on cost creation in the context of six types of capital, in particular, social. In turn, the distribution of financial and non-financial reporting stops to be relevant because such reporting is not sufficiently accessible, objective and incapable of meeting the information needs of all stakeholders. Therefore, the «Management Report» can positively affect the quality of reports published by Ukrainian enterprises and contribute to the development of integrated reporting.